2016
DOI: 10.1016/j.palaeo.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A meta-database of peatland palaeoecology in Great Britain

Abstract: We present and appraise a large compilation of peatland palaeoecological research in Great Britain, and discuss the value of these data for secondary analysis. We identify 475 radiocarbon-dated palaeoecological records from British peatlands published since 1970. Peatland palaeoecological research has been widespread but with some clear spatial biases reflecting factors such as accessibility and the location and interests of active researchers. We show that basic details such as stratigraphic descriptions, sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…2007; Tipping 2008b). None of this alters the fact that blanket peat is a major sedimentary and visual element of the Scottish landscape, and provides an important palaeoenvironmental archive (Payne et al 2016). Even if the level of anthropogenic involvement with its spread remains unresolved, there is little doubt that humans used the peat, in the past as now (Fig.…”
Section: Blanket Peatmentioning
confidence: 99%
See 1 more Smart Citation
“…2007; Tipping 2008b). None of this alters the fact that blanket peat is a major sedimentary and visual element of the Scottish landscape, and provides an important palaeoenvironmental archive (Payne et al 2016). Even if the level of anthropogenic involvement with its spread remains unresolved, there is little doubt that humans used the peat, in the past as now (Fig.…”
Section: Blanket Peatmentioning
confidence: 99%
“…Apart from dating issues and the decision as to what constitutes blanket peat, we already know from intra-site studies that topographic variation makes it difficult to determine what would equate to representative dates for an area (e.g., a slope or a larger area) as opposed to a particular site, given the time-transgressive nature of peat spread (Charman 1992;Lawson et al 2007;Tipping 2008b). None of this alters the fact that blanket peat is a major sedimentary and visual element of the Scottish landscape, and provides an important palaeoenvironmental archive (Payne et al 2016). Even if the level of anthropogenic involvement with its spread remains unresolved, there is little doubt that humans used the peat, in the past as now (Fig.…”
Section: Blanket Peatmentioning
confidence: 99%
“…We make contributions from four sources: 1) Firstly, to the published dataset we added data previously compiled by Payne et al (2016) for peatland sites across Britain. This study identified 475 radiocarbon dated peatland sites of which 186 are in England.…”
Section: Stepsmentioning
confidence: 99%
“…Building such compilations also provides a useful opportunity to evaluate the 'state of the art' and assess trends, biases and gaps in the research which is undertaken and published. Previous databases covering the United Kingdom have focussed on specific environments such as lakes (Battarbee et al 2011) or peatlands (Payne et al 2016) or on specific methods such as pollen analysis (Fyfe et al 2009) or tephra (Newton et al 2007). Recently Suggitt et al (2015a) presented an English Sediment Core Metadatabase (ESCM) with the goal to ' determine as many sediment coring sites in England as possible' with a particular focus on the Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the extent to which these processes are occurring in mire ecosystems depends on analyzing how the composition and structure of mire vegetation responds to environmental changes over the long term. The primary evidence for such long‐term dynamics is provided by the numerous paleoecological studies that have been conducted in peatlands (Payne et al., 2016). Recent research has tended to focus on assessing peatland development and the impacts of climate change during the late Holocene, employing techniques including palynology, macrofossil analysis, testate amoebae, isotopes, and biomarkers (Blundell & Holden, 2015).…”
Section: Introductionmentioning
confidence: 99%